Corporate governance and risk management in the financial industry: changes after the global financial crisis - Ojo, Abosede Omolola (2016)
This research investigates how corporate governance and risk management in financial industry affects the performance of companies. This study distinguishes between the pre-crisis and post-crisis periods to determine whether the global financial crisis of 2008 significantly affects corporate governance and risk management of financial industry. In addition, this research also tests how the effects of corporate governance and risk management factors on the performance of banks and insurance companies changed after the financial crisis. The study focuses on the 50 companies in the European union including banks and insurance companies. The study measures the profitability of companies through ROA. Risk management factors are the size of a risk committee in relation to board size and the presence of a Chief Risk Officer. Corporate governance factor is board structure measured as board independence. Besides, the mode incorporates leverage, size, industry, and loan to assets variables. The findings demonstrate that corporate governance and risk management were not associated with the profitability of financial institutions both before and after the global financial crisis. The effects were captured only for control variables such as size, leverage, and loan to assets ratio. The result shows that all these factors negatively affected ROA. Moreover, banks faced lower ROA ratios than insurance companies. This study also shows that corporate governance and risk management characteristics significantly changed after the financial crisis. More companies tend to include a CRO in their structure, having more independent boards, and increase the size of their risk management committees.